Empagliflozin alleviates atherosclerotic calcification by inhibiting osteogenic differentiation of vascular smooth muscle cells - Li, Junping; Li, Changping; Huang, Zhaoqi; Huang, Chunling; Liu, Juanzhang; Wu, Tao; Xu, Shuwan; Mai, Peibiao; Geng, Dengfeng; Zhou, Shuxian; Zhang, Kun; Liu, Zhaoyu (Frontiers in Pharmacology, 2023)
SGLT-2 inhibitors, such as empagliflozin, have been shown to reduce the occurrence of cardiovascular events and delay the progression of atherosclerosis. However, its role in atherosclerotic calcification remains unclear. In this research, ApoE -/-mice were fed with western diet and empagliflozin was added to the drinking water for 24 weeks. Empagliflozin treatment significantly alleviated arterial calcification assessed by alizarin red and von kossa staining in aortic roots and reduced the lipid levels, while had little effect on body weight and blood glucose levels in ApoE -/-mice. In vitro studies, empagliflozin significantly inhibits calcification of primary vascular smooth muscle cells (VSMCs) and aortic rings induced by osteogenic media (OM) or inorganic phosphorus (Pi). RNA sequencing of VSMCs cultured in OM with or without empagliflozin showed that empagliflozin negatively regulated the osteogenic differentiation of VSMCs. And further studies confirmed that empagliflozin significantly inhibited osteogenic differentiation of VSMCs via qRT-PCR. Our study demonstrates that empagliflozin alleviates atherosclerotic calcification by inhibiting osteogenic differentiation of VSMCs, which addressed a critical need for the discovery of a drug-based therapeutic approach in the treatment of atherosclerotic calcification.